Synthesis of Natural Zeolite/ZnO and its photodegradation activity on congo red - M. Pranjoto Utomo; A. K. Prodjosantoso; Kun Sri Budiasih; Isti Yunita; Tisia Miftakhul Triani; Vera Dwi Nur Rahmawati (Universitas Negeri Yogyakarta, 2023)
Dyes are the most common compound used in the textile industry. Dyes consisted of azo compound that is difficult to be degraded. Undegradated azo compound, such as congo red, danger for the environment. An alternative effort to handle congo red waste must be conducted. Natural zeolite/ZnO is a material that can be used to degrade congo red to be simpler compound. Based on the analysis, the characters of natural zeolite/ZnO are hexagonal wurtzite structure, particle size 24.264 nm, band gap energy 2.96 eV. The highest degradation percentage in photodegradation activity of natural zeolite/ZnO on congo red is 99.41%.